+0  
 
0
48
1
avatar

If \($f(x)=\dfrac{a}{x+2}$\), solve for the value of a so that \(f(0)=f^{-1}(3a)\).

Guest May 5, 2018
Sort: 

1+0 Answers

 #1
avatar+26689 
0

To get f-1 rewrite f as:

 

   \(f=\frac{a}{x+2}\\x+2=\frac{a}{f}\\x=\frac{a}{f}-2\)

 

Now change f into x and x into f-1:

\(f^{-1}=\frac{a}{x}-2\)

 

We have: \(f(0)=\frac{a}{2}\text{ and }f^{-1}(3a)=\frac{a}{3a}-2\rightarrow-\frac{5}{3}\)

 

I'm sure you can take it from here!

Alan  May 5, 2018

9 Online Users

New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy